DAYA SAING INDUSTRI FARMASI HALAL DI INDONESIA, MALAYSIA, DAN ARAB SAUDI: ANALISIS BERDASARKAN SGIE 2024/2025 - Ario Putra, Fakhri Muhammad; Rindyana, Wulan; Anshari, Al (Taksasila Edukasi Insani, 2026)
This study analyzes the development of the halal pharmaceutical sector in Indonesia, Malaysia, and Saudi Arabia based on differences in halal regulations, production localization capacity, research and innovation ecosystems, and trade performance, referenced from the SGIE 2024/25 report and related academic literature. The study aimed to explain variations in national strategies and levels of institutional readiness in strengthening the halal pharmaceutical industry in the three countries. The study employed a comparative qualitative approach with secondary data sources through document analysis and thematic content analysis of regulatory indicators, halal certification, manufacturing localization, research collaboration, and industrial competitiveness. The results indicate that Indonesia is at the stage of strengthening localization and import substitution with gradual integration of halal certification, Malaysia has more mature halal governance with export-oriented industrial capacity, while Saudi Arabia is in the transition phase toward manufacturing independence through production localization and technological partnerships. The study concluded that the maturity of halal regulations, technological capacity, and research and industrial integration are the main determinants of the competitiveness of the halal pharmaceutical sector across countries. Keywords : halal pharmaceuticals, SGIE, halal regulations, production localization